The Lifetimes of Evaporating Sessile Droplets of Water Can Be Strongly Influenced by Thermal Effects - Feargus G. H. Schofield; David Pritchard; Stephen K. Wilson; Khellil Sefiane (Fluids, 2021)
The effect of the thermal properties of the system on the lifetime of an evaporating sessile droplet of water is analysed using a fully coupled model which involves determining the temperature of the droplet, the substrate and the atmosphere. The evolutions, and hence the lifetimes, of droplets of water evaporating in both of the extreme modes are calculated. In particular, it is shown how the lifetimes of droplets of water can be strongly influenced by thermal effects. Droplets with larger initial contact angles or on less conductive substrates generally have longer lifetimes than those with smaller initial contact angles or on more conductive substrates, and the physical mechanism by which the thermal properties of the system influence the evaporation can be understood in terms of the thermal anchoring between the droplet and the lower surface of the substrate.